TINY HEARTS, BIG LESSONS: UNDERSTANDING THE FACTORS SHAPING VALUES IN EARLY CHILDHOOD - Kabadayi, Abdülkadir (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The acquisition of values at an early age is influenced by a myriad of factors that shape children’s moral development and ethical reasoning. Family dynamics, cultural influences, social interactions, and individual characteristics all play significant roles in shaping children’s understanding of right and wrong, empathy, and social responsibility. Positive role modeling, open communication, cultural awareness, and moral education are key components in fostering values acquisition during the formative years. Understanding the complex interplay of these factors is essential for promoting positive character development and moral education in young children. The aim of this article is to put forward the factors that affect the acquisiton of the values at an early year.